Mast cell disorders: From infancy to maturity. Issue 1 (28th November 2018) - Wilcock, Amy; Bahri, Rajia; Bulfone‐Paus, Silvia; Arkwright, Peter D.
Abstract: Mast cells are typically linked to immediate hypersensitivity and anaphylaxis. This review looks beyond this narrow role, focusing on how these cells have evolved and diversified via natural selection promoting serine protease gene duplication, augmenting their innate host defense function against helminths and snake envenomation. Plasticity of mast cell genes has come at a price. Somatic activating mutations in the mast cell growth factor KIT gene cause cutaneous mastocytosis in young children and systemic mastocytosis with a more guarded prognosis in adults who may also harbor other gene mutations with oncogenic potential as they age. Allelic TPSAB1 gene duplication associated with higher basal mast cell tryptase is possibly one of the commonest autosomal dominantly inherited multi‐system diseases affecting the skin, gastrointestinal tract, circulation and musculoskeletal system. Mast cells are also establishing a new‐found importance in severe asthma, and in remodeling of blood vessels in cancer and atherosclerotic vascular disease. Furthermore, recent evidence suggests that mast cells sense changes in oxygen tension, particularly in neonates, and that subsequent degranulation may contribute to common lung, eye, and brain diseases of prematurity classically associated with hypoxic insults. One hundred and forty years since Paul Ehrlich's initial description of "mastzellen, " this review collates and highlights the complex and diverse roles that mast cells play in health and disease.